Iranian Cottonseed Meal Varieties As Substitute For Soybean Meal In Rainbow Trout(Oncorhynchus Mykiss) Feeds - Dadgar, Shahram (2009)

(untitled)
This study was set up to investigate the nutritional value and the optimum inclusion level of several Iranian cottonseed meals i.e. var. Pak, Sahel and Akra (CSMP, CSMS, and CSMA) as a substitute for soybean meal (SBM) in rainbow trout (Oncorhynchus mykiss) feed. Apparent digestibility coefficients (ADC) were calculated in experiment 1 by using an indigestible marker. At the end of this experiment, the ADCs of CSMP, CSMS, CSMA and SBM were measured. Results showed that ADC values for most nutrients of CSMP, CSMS, and CSMA were different from those of SBM and when the varities were compared; ADC values for CSMP (62.7% from DM and 82.4% for CP and 66.6% for crude fat) were higher than the two other CSM varieties i.e. CSMS and CSMA. Three separate studies were carried out to investigate the nutritional value of each Iranian cottonseed meal varieties ( CSM) as soybean meal substitute in quality low cost rainbow trout feeds. Six formulated feeds consisting different substitution levels (0, 20, 40, 60, 80, 100%) of SBM with CSMP, CSMS, and CSMA, respectively, were fed to a total of 540 rainbow trout with initial mean body weight of 50 ± 5 g. Fish were randomly stocked into eighteen 100 L. fiberglass tanks with 30 fish per tank and 3 tanks per diet and fed to apparent satiation 3 times a day and 7 days per week for